Policy Implementation Challenges of the Online Single Submission Risk-Based Approach for MSMEs: Lessons from North Gorontalo Regency - Grace Parlin D. Mangosa; Rauf A. Hatu; Moh. Hidayat Koniyo; Udin Hamim (Journal Public Policy, 2026)
The purpose of this study is to analyze the implementation of the Online Single Submission Risk-Based Approach (OSS RBA) permitting services for Micro, Small, and Medium Enterprises (MSMEs) in North Gorontalo Regency and to formulate an implementation model that is adaptive to local conditions. This research employed a qualitative descriptive-analytical method, with data collected through in-depth interviews, field observations, and document analysis involving policy implementers and MSME actors. The analytical framework was based on Edwards III’s policy implementation model, which emphasizes communication, resources, implementer disposition, and bureaucratic structure. The results of the study indicate that the implementation of OSS RBA has not yet been fully effective. Significant challenges include weak policy communication, limited human resources and digital infrastructure, insufficient technical capacity among implementers, and a bureaucratic structure that remains centralized and less responsive to the region's geographical and socio-economic characteristics. These conditions contribute to limited access, low understanding, and varying levels of acceptance among MSMEs toward digital-based licensing services. The study concludes that effective implementation of OSS RBA requires a locally context-based implementation model that integrates strengthened communication, capacity building for implementers, improved digital infrastructure, and a more inclusive bureaucratic structure involving sub-districts and villages. This adaptive model positions OSS RBA not only as an administrative instrument but also as a tool for MSME empowerment and local economic development.